Pengaruh dan Efektivitas Media Sosial pada Proses Pengumpulan Zakat, Infaq, dan Sedekah: Studi Kasus di Lembaga Amil Zakat Al-Washliyah Beramal (LAZ WASHAL)) Sumatera Utara - Yusnita Ulfah Munthe; Fauzi Arif Lubis (Universitas Muhammadiyah Enrekang, 2022)
Along with the times, social media technology plays an important role in the development of human life. One of the important roles of social media is as a means of promotion. The high number of social media users makes social media a very influential and effective promotional tool for its users, including the North Sumatera Amil Zakat Foundation (LAZ WASHAL) which utilizes and uses social media as a means of promotion in collecting zakat, infaq and alms funds from donors or Muzakki. This writing aims to find out how the influence and effectiveness of social media on the process of collecting zakat, infaq and alms at LAZ WASHAL. The philosophy and value system about why this instruction was formed, the rationale and what it wants to achieve in the management of zakat, infaq and alms, namely wanting to help reduce poverty.